Type specimens of Anthus berthelotii Bolle, 1862 (Aves: Motacillidae) - Mlíkovský, Jiří; Frahnert, Sylke; Loskot, Vladimir M. (Zootaxa, 2013)
Berthelot’s Pipit Anthus berthelotii Bolle, 1862a, an endemic to Macaronesia (see e.g. García-Talavera Casañas 1999 for this term), is closely related to the widespread Palearctic Anthus campestris (Linnaeus, 1758) (Alström & Mild 1993; Arctander et al. 1996; Illera et al. 2007; Voelker 1999a,b). Carl August Bolle (1821–1909), German traveler and naturalist, visited Macaronesia in 1851–1853 and again in 1856–1857 (Salinger & Strehlow 1891; see also Bolle 1854a,b, 1857, 1858a,b, 1862a,b). He described Anthus berthelotii in two papers (Bolle 1862a,b), providing a morphological description of the species and referring to several authors who, he believed, recorded the same species under different names. However, he did not mention specific specimen(s) or collection(s) at which he had studied Anthus specimens. Thus, we restudied the original description of Anthus berthelotii to identify its type series.